2021
DOI: 10.1111/trf.16291
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of SARS‐CoV‐2 antibodies in 8000 U.S. first‐time convalescent plasma donations

Abstract: Background Coronavirus disease 2019 (COVID‐19) convalescent individuals carry antibodies against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) that, through a plasma donation, can be used as a potential therapeutic either in direct transfusion or for the manufacture of hyperimmune globulin (HIG). The success of such interventions depends on the antibody potency in such plasma donations, but little information on the collection of potent units is currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Findings in other studies with BNT162b2 are inconsistent [ 21 , 22 , 23 ]. Likewise, it remains inconclusive how sex correlates with SARS-CoV-2 antibody response in COVID-19 patients as studies in convalescent plasma donors describe different outcomes [ 24 , 25 , 26 ]. We assume that selection bias plays an important role when comparing antibody levels—both in vaccinees and convalescent plasma donors—and may lead to opposite findings.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in other studies with BNT162b2 are inconsistent [ 21 , 22 , 23 ]. Likewise, it remains inconclusive how sex correlates with SARS-CoV-2 antibody response in COVID-19 patients as studies in convalescent plasma donors describe different outcomes [ 24 , 25 , 26 ]. We assume that selection bias plays an important role when comparing antibody levels—both in vaccinees and convalescent plasma donors—and may lead to opposite findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus of high interest how currently manufactured IVIG/SCIG can serve these immunodeficient patient groups in terms of protection against a SARS-CoV-2 infection or impeding disease severity of COVID-19. First reports of anti-SARS-CoV-2 reactivity and neutralization capacities in commercially produced immunoglobulins have already been published [ 29 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean IgG antibody ratios started to increase on the 29 th day up to the 112 th day, after which they followed a decreasing trend, although their presence was still observed up to the 244 th day. In the study by Karbiener et al 29 most of the CP donations were made between days 20-95 following COVID-19, and the mean IgG antibody ratios were noted to increase on the 20 th day up to the 36 th day, decreasing slowly until the 95 th day. Likewise, the persistence of antibody response was reported up to the 168 th ( Maine et al 30 ), 195 th (Gaebler et al 25 ), 210 th (Mai et al 26 ), and 240 th days ( Dan et al 27 ) by indicated authors.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, a significant association was noted between the mean IgG antibody ratios and BMIs according to the WHO categorization 35 and the highest mean IgG antibody ratio was identified in those with BMI ≥30 kg/m 2 , followed by those with BMI 25-29.9 kg/m 2 , BMI 18.6-24.9 kg/m 2 and BMI <18.5 kg/ m 2 . In some studies, it was emphasized that a significant positive association existed between body weight and SARS-CoV-2 antibody titers 23,29,36 .…”
Section: Discussionmentioning
confidence: 99%